Time-tabling scheduling for educational institution - Mohd Shah Baki, Shah Rizam; Hashim, Habibah; Abdul Aziz, Mohd Azri; Mahmood, Abdul Razak (2002)
This project presents the structured and computerised steps in the making of timetable for educational institutions. The system provides facilities to the timetable maker with a userfriendly interface and flexible end-user requirement. Each step in the making of the timetable is carefully studied and clearly defined to produce the well-structured steps. The steps involved were then computerised to enhance the process of the making of the timetable. The system was developed using Visual Basic and all the related data were save in the Access Database. The data validation concept and the database design and query strategy were adopted smartly in ensuring the successfulness of this project. The system is found to be very efficient since it has manages to reduce the time taken to produce a well-looks timetable.